Enhancing Junior High School Students’ Motivation in Physics Learning through Kahoot! Based Gamification: An ARCS Model Approach - Maria Yuliana Kua; Egidius Dewa; Yohana Patricia Pedhu Lobe (Universitas Muhammadiyah Makassar, 2025)
Motivation plays a pivotal role in shaping students’ engagement and achievement, particularly in subjects such as physics that are often perceived as difficult and abstract. Numerous studies have shown that low motivation among junior high school students contributes to poor performance and limited participation. This highlights the urgency of innovative instructional approaches that can foster interest and persistence. Gamification has emerged as a promising solution, with platforms such as Kahoot! providing interactive features designed to increase student engagement through competition, feedback, and collaboration. The objective of this study was to examine the effectiveness of Kahoot!-based gamification in enhancing students’ learning motivation in physics, measured comprehensively using Keller’s ARCS model (Attention, Relevance, Confidence, and Satisfaction). A quasi-experimental design with a one-group pretest–posttest approach was employed, involving 175 eighth-grade students from six junior high schools in East Nusa Tenggara, Indonesia. Data were collected through a validated ARCS-based motivation questionnaire and analyzed using descriptive statistics, the Wilcoxon Signed-Rank Test, effect size calculation, and normalized gain (N-Gain). The findings revealed a significant increase in students’ motivation, with overall scores rising from 3.15 to 4.10, a large effect size (r = 0.85), and a medium N-Gain (0.51). The greatest improvement occurred in attention, while satisfaction increased the least. These results confirm that Kahoot! effectively improves multiple dimensions of motivation and demonstrates its value as an innovative tool for fostering interactive, student-centered learning in physics. The novelty of this study lies in applying the ARCS framework to analyze gamification outcomes in junior high school physics. The contribution of this study lies in demonstrating that gamification, particularly through Kahoot!, can effectively enhance multiple dimensions of learning motivation in physics. Furthermore, the findings enrich the body of knowledge on gamification in science education and present valuable implications for improving physics learning in Indonesia and comparable educational contexts.